2009
DOI: 10.1016/j.ecolecon.2009.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the major drivers of the ecological footprint using the STIRPAT model and the PLS method—A case study in Henan Province, China

Abstract: Taking Henan Province of China as an example, we computed and analyzed the ecological footprint (EF) in . The results showed that the EF in Henan Province quadrupled in the 23 years, but its ecological carrying capacity (EC) was rather low and was in a state of slow decline, indicating that Henan's ecological deficit (ED) had become a remarkable social problem. Therefore, the major drivers of the EF's change were analyzed. According to the simulations with STIRPAT model, the major drivers of Henan's EF were hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(66 citation statements)
references
References 19 publications
(19 reference statements)
2
51
0
4
Order By: Relevance
“…Additional factors can be added to the basic STIRTPAT model (York et al 2003;Dietz et al 2007;Jia et al 2009). The specific and measurable factors which may have influenced the EF include: total population (P), GDP per capita (A 1 ) and the quadratic term of GDP per capita (A 2 ), percent of GDP from industry (T 1 ), urbanization rate (T 2 ) and the quadratic term of T 1 (T 1 ' ) and of T 2 (T 2 ' ), fixed assets investment, energy intensity and others.…”
Section: Major Driving Forces Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Additional factors can be added to the basic STIRTPAT model (York et al 2003;Dietz et al 2007;Jia et al 2009). The specific and measurable factors which may have influenced the EF include: total population (P), GDP per capita (A 1 ) and the quadratic term of GDP per capita (A 2 ), percent of GDP from industry (T 1 ), urbanization rate (T 2 ) and the quadratic term of T 1 (T 1 ' ) and of T 2 (T 2 ' ), fixed assets investment, energy intensity and others.…”
Section: Major Driving Forces Analysismentioning
confidence: 99%
“…They showed that population size and affluence are the principal drivers of anthropogenic environmental stressors. Jia et al (2009) andWang et al (2010) used STIRPAT to identify the major drivers of EF in Henan Province and Jilin Province respectively and showed that the model is an effective way to assess sustainability of anthropic systems (Wang et al 2010). They modified the STIRPAT model to a logarithmic regression model (York et al 2003), using OLS (ordinary least square) regression method to calculate the coefficients of independent variables.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, a quantitative exploration of drivers related to cement consumption is urgent that can facilitate national decision makers and local urban planners to track cement consumption trend, to formulate management strategies and policies, and then to promote the development of resource-saving and environment-friendly city. Recently, the STIRPAT model has been extensively harnessed by researchers in economic environmental analysis for its extendibility (Fan et al, 2006;Ji and Chen, 2015;Jia et al, 2009;Lin et al, 2009;Liu et al, 2015;Shahbaz et al, 2016;Wang et al, 2013a). These studies, however, rarely concern about which factors are driving or reducing regional cement consumption in China.…”
Section: Introductionmentioning
confidence: 99%
“…This method combines the features of principal component analysis and multiple linear regression (Abdi, 2010) and can produce regression models, provide a correlation analysis and simplify data structure in one algorithm (Wang, 1999). This approach is particularly useful when independent variables display strong collinearity (Wang, 1999(Wang, , 2006Jia et al, 2009). Ordinary multiple regression models are often limited by the sample size.…”
Section: Data Analysesmentioning
confidence: 98%